THE IMPORTANCE OF ENGLISH LEARNING MEDIA IN IMPROVING LEARNING ACHIEVEMENT - Zaini Hasan (Jurnal Penelitian Progresif, 2024)
English teachers play a crucial role in daily learning activities at school, as they are responsible for designing, managing, implementing, and evaluating learning activities. Additionally, the role of English teachers in the learning process is highly strategic and decisive. This is because teachers determine the depth and breadth of the subject matter, as they select and choose the materials, methods, and media to be presented to students. English teachers indeed play the most important role in the learning process, so they are regarded as central figures or key players in the world of education.